2002
DOI: 10.1097/00000637-200211000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Normal-Mode Ruby Laser and the Combined (Normal-Mode Plus Q-Switched) Ruby Laser in the Treatment of Congenital Melanocytic Nevi: A Comparative Study

Abstract: The effect of the normal-mode ruby laser (NMRL) and the combined (normal mode plus Q-switched) ruby laser on congenital melanocytic nevi (CMN) was evaluated, and the degree to which both laser treatment regimens remove melanocytes was compared in 15 patients. Each nevus was marked to designate half of the lesion for the NMRL treatment and half of the lesion for combined ruby laser treatment. The efficacy of each laser treatment was correlated with the degree of clinical improvement determined by photographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 22 publications
0
45
0
Order By: Relevance
“…The degree of lightening of the lesions was assessed by a red-green skin reflectance spectrometer (Dermaspectrometer, Cortex Technology, Hagland, Denmark) [8]. The mean of melanin index (MI) measurements taken from the lentigines before (MI Pre ), 4 weeks after laser irradiation (MI Post ) and the adjacent normal skin (MI Normal ) was calculated.…”
Section: Assessment Of Responsementioning
confidence: 99%
“…The degree of lightening of the lesions was assessed by a red-green skin reflectance spectrometer (Dermaspectrometer, Cortex Technology, Hagland, Denmark) [8]. The mean of melanin index (MI) measurements taken from the lentigines before (MI Pre ), 4 weeks after laser irradiation (MI Post ) and the adjacent normal skin (MI Normal ) was calculated.…”
Section: Assessment Of Responsementioning
confidence: 99%
“…7 Funayama et al reported significant pigment removal of giant CMN in six patients using combined pulsed dye laser and QS ruby laser treatment with minimal scarring, but the average number of treatments necessary was 7.7 sessions. 11 Our patient with giant CMN achieved good (51-75%) reduction of pigment after only one session of combined Er:YAG/LP-Alex laser treatment, and no signs of malignant transformation in the treated area were seen in follow-up. Near complete clearance of pigment was achieved in areas relatively lighter in color, but pigmented nevomelanocytic nests might persist in the deeper dermal layers in darker areas, which would require further treatment sessions.…”
Section: Discussionmentioning
confidence: 58%
“…In order to solve this problem, many studies have utilized ruby lasers in various combinations of different modes, including normal mode, QS mode, and long-pulsed mode. 5,[11][12][13][14][15] Some of these studies reported good results, although multiple treatment sessions were required.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment failures with QSRL are thought to result from their short pulse durations and limited depth of penetration (1 mm). 53,68,69 Ueda et al 70 suggested that long-pulsed lasers might allow more heat dispersion to surrounding cells, allowing for more effective targeting of nevus nests, including nonpigmented melanocytes rather than individual nevus cells. 70 Studies using NMRLs have shown efficacy at nevus clearance of small to giant sized CMN in Japanese patients.…”
Section: Ruby Lasermentioning
confidence: 99%